Pengaruh Perbandingan Puree Pepaya (Carica papaya L.) dan Puree Jeruk Manis (Citrus Sinensis L.) Terhadap Karakteristik Selai - Satria Prananda, I Putu Angga; Sugitha, I Made; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
This research aimed to measure the effect of papaya and sweet orange ratio on the characteristics of the jam and to determine the exact ratio of papaya and sweet orange to produce jam with the best characteristics which is liked by panelists. This research used a completely randomized design with papaya and sweet orange ratio treatment consisting of 5 levels, such as 100%: 0%, 80%: 20%, 60%: 40%, 40%: 60%, and 20%: 80%. Each treatment was repeated three times, so that 15 experimental units were obtained. The data obtained were analyzed by analysis of variance and if there is a treatment effect, it will be further tested with Duncan's test. The results showed that the papaya and sweet orange ratio had a very significant effect on water content, total soluble solids, reducing sugar, beta carotene, vitamin C, viscosity, and pH, had a very significant effect on texture, color and aroma characteristics, had a significant effect on preference color and aroma, and did not significantly affect the preference for texture, taste, and overall acceptance. The ratio of 80% papaya and 20% sweet orange is the best treatment with chemical characteristics of water content 45.948%, reducing sugar 30.478%, beta carotene 1.503%, vitamin C 1.0833%, total soluble solids 53.0% brix, viscosity 1766.66 mPa.s, and pH 3,056, as well as sensory characteristics which include texture was slightly liked, color was slightly liked, aroma was slightly liked, taste was slightly liked, and overall acceptance was slightly liked.